Rationale behind EU-DEMO limiter's plasma-facing component design under material phase change - Richiusa, ML; Ireland, P; Nicholas, J; Vizvary, Z (IEEE, 2022)
The protection strategy adopted for the European DEMOnstration (EU-DEMO) fusion power reactor foresees the use of sacrificial components-referred to as limiters-dealing with plasma-wall contacts. Their aim is to protect the first wall (FW) against the huge amount of plasma energy (up to GigaJoules) released in a few milliseconds during disruptive events, which might lead to melting and/or vaporization of the foreseen plasma-facing tungsten armor. The current limiter design concepts rely on actively water-cooled plasma-facing components (PFCs) made of tungsten. As water is not allowed inside the main chamber, limiter's PFCs must be designed to preserve the cooling system integrity under any scenario, therefore the estimate of the thickness of material undergoing any phase change is crucial. Given the initial assessment of plasma magnetic configurations during off-normal events, this article describes the procedure followed for designing the limiter's PFC, which includes a novel approach for estimating the molten thickness of material under high heat flux. A simplified 1-D model has been implemented in MATLAB, which deals with multiphase moving boundary problems, hence its name Thermal Analysis foR Tracking InterFaces under meLting&vaporizaTion-induced plasma Transient Events (TARTIFL&TTE). This model takes its inspiration from the way phase change interface tracking problems are tackled in food industry (i.e., freeze-drying processes) and solute concentration diffusion-controlled problems. It overcomes the complexity of solving a strongly coupled non-linear system of partial and ordinary differential equations in moving spatial domains by adopting a change of coordinate system based on the Landau transformation. As a result, an equivalent and fixed spatial coordinate system is defined where the spatial domain boundaries of the different phases are constrained, and the systems of governing equations are easy to solve. Both the solid and liquid phases are modeled, while the vapor is assumed to be removed once formed. Its benchmark against computational results found in the literature has shown a very good agreement, which paves the way to further development of it. For phase change interface tracking problems in 2-D/3-D and more complex geometries, a commercial Multiphysics software adopting the Lagrangian-Eulerian approach in moving mesh frames will be used for tackling problems where material is removed following a phase change. Although the vapor domain is not simulated, a set of gas kinetics boundary conditions couples the interface between vapor and liquid phases, driving its position over time. This will be detailed described in a future companion article.